Hepatitis B and C virus in West-Central Turkey: Seroprevalence in healthy individuals admitted to a university hospital for routine health checks - Neşe DEMİRTÜRK; Tuna DEMİRDAL; Dilek TOPRAK; Mustafa ALTINDİŞ; Orhan Cem AKTEPE (Turkish Journal of Gastroenterology, 2019)
-